The Implementation of Scientific Approach to Improve Mathematical Understanding Ability on Senior High School Students - Helmi Ilham Nabila; Harry Dwi Putra; Heris Hendriana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematical understanding ability is a basic ability that must be possessed by every student in understanding the concept of material and applying it in a mathematical symbol and formula. However, the fact is that currently the failure in learning mathematics is due to students' lack of understanding of the concepts in mathematics material. The purpose of this study was to see the improvement of mathematical understanding ability of class VIII-B students on the material of Two-Variable Linear Equation System at SMPN 1 Margaasih. The research method used is the model of Kemmis and McTaggart with the subject studied, namely students of class VIII-B SMPN 1 Margaasih. The research conducted used Classroom Action Research (CAR). The research took place over 2 cycles, each cycle consisting of several stages starting from the plan, action, observation and reflection stages. In cycle I and cycle II the teacher gave a test, besides that in each cycle an observation sheet was provided. The results of this study showed that there was an increase in the completeness of learning scenarios for teachers by 51.92% and for students by 50.01%. In addition, the results of filling out the tests given each cycle showed good results with the number of students who scored above the KKM in cycle I by 69.44% and cycle II by 80.55%, meaning an increase of 11.11%. Thus, the mathematical understanding ability of class VIII students on Two-Variable Linear Equation System material at SMPN 1 Margaasih using a scientific approach has improved.